Sistema nacional de avaliação da educação básica: situando olhares e construindo perspectivas - Santos, Regina Lúcia Lourido dos (2007)
The present paper aims to analyze critically the different documental sources that refer to SAEB Sistema Nacional de Avaliação da Educação Básica ( National System for Evaluation of Basic Education). It tries to question and makes suggestions that contribute to the building of an alternative educational evaluation policy which opposes SAEB, taking into account its limitations to show the quality of Basic Education in Brazil. A qualitative theoretical documental survey was done. Discourse analysis elements were used based on fundamental data sources such as: official documents, educational articles in Journals, newspapers articles. Our analysis was based on some contributions of theoreticians who have a critical stand. This paper highlights that SAEB s policy represents a step back concerning the theoretical advance in the field of educational evaluation, which is worrying if its influence on evaluative policy of States and Municipals is taken into account. This paper detected that there are questionings and even some suggestions to SAEB. This paper evidenced that the logic of the examination gets stronger day by day which requires a reflection-action of the subjects that were committed to a perspective of evaluation that considered the complexity of the educative process